DYNAMICS AND PROSPECTS OF INCREASING THE INFLUENCE OF OPENNESS TO EXPERIENCE IN THE HIGHER EDUCATION SYSTEM (American Journal of Pedagogical and Educational Research, 2023)
In the article, in the twenty-first century - the age of intelligence, teachers and their learning of scientific research in education, the master of their profession, Pedagogical skills, Spiritual and ideological maturity, loyalty to their profession, considering it as the meaning of their lives, patriotism, national pride, inclination to science, knowledge, organization , open relations such as politeness, communicativeness, and the ability to attract students to themselves, arouse their enthusiasm, inculcate the idea of national modernity, and inspire them to national-educational tasks.